Aggressive treatment of cerebral venous sinus thrombosis (CVT) with stent retrievers and local thrombolysis: why we need a registry - Kowoll, Christina Maria; Lockau, Hannah; Dorn, Franziska; Dohmen, Christian (Fortschritte der Neurologie · Psychiatrie, 2017)
Purpose Anticoagulation is the first-line therapy for cerebral venous sinus thrombosis (CVT). Endovascular treatment is increasingly applied in patients deteriorating despite anticoagulation with extensive thrombosis or contraindications for anticoagulation. Experience with stent retrievers in CVT is limited.Results We present three cases of severe CVT treated with stent-retrievers, thrombus aspiration and local thrombolysis. In two patients with extensive thrombosis, a partial recanalization was achieved, but only one of them showed significant improvement. Despite failed recanalization, the third patient recovered completely.Conclusions Limited experience with three cases indicates that recanalization may not necessarily result in favourable clinical outcome even in severely affected patients. Therefore, invasive procedures such as local thrombolysis and thrombectomy remain individual therapeutic options when anticoagulation fails and in patients with extensive thrombosis.
Keywords: cerebral venous sinus thrombosis; thrombectomy; thrombolysis; stent; Solitaire; Trevo